Impacts of Feeding BOSPROTM on Reproduction and Lactation Performance of Lactating Holsteins - Preeyaphan Udomprasert,; Thaveewat Tassanawat,; Thanasorn Thipayarak, (Agriculture and Natural Resources, 1993)
A cross sectional study was conducted in a 124-Holstein herd in which 98 cows were milking. Average milk production/cow/day (MW), roughage types, percent fat of a bulk tank sample, climatic factors including relative humidity, minimum and maximum temperatures, and a dummy variable (BP) indicating the addition of BOSPROTM in the ration, were recorded on a daily basis. Two linear models were used to demonstrate the effects of each independent variable, particularly the BP variable, on the two dependent variables, MW and MW adjusted to 4 % fat (FCM). The BP variable was always put last into the linear models. Including BOSPROTM into the ration was likely to improve MW by 0.905 kilograms (kgs) and FCM by 0.907 kgs (P≤0.01), where the grand means of MW and FCM were 12.803 and 13.257 kgs respectively. In addition, the minimum temperature was the climatic factor closely associated with FCM. For every 1°C increment in minimum temperature, FCM declined by 0.043 kgs (P≤0.05). A control experiment was conducted concomittantly with the cross sectional study. Early lactating cows were randomly assigned into two groups such that the averages of days in milk, lactation number, body weight and milk/cow/ day were not significantly different. Equal amounts of roughage and concentrate were given to cows in both groups, Any feed left in the bunk was weighed back in the morning and evening if necessary. The cows in treatment group recieved 30 grams of BOSPROTM per day for one month. MW and body weight (BW) of each cow was measured on a weekly basis. BOSPROTM turned the slope of the lactation curve of treatment group to positive while that of control group was negative. The cows in treatment group gave 2.09 kgs more milk than those in control group. When milk price was 7.50 bahts/kg and 30 grams of BOSPROTM cost 3 baths, BOSPROTM generated 4.37 bahts for 1 baht invested. The body weight change and reproductive performance in both groups were similar.